Procalcitonin-Guided Antibiotic Treatment in Lower Respiratory Tract Infections - CEYHAN, BERRİN; BALCAN, MEHMET BARAN; OLGUN YILDIZELİ, ŞEHNAZ (GALENOS YAYINCILIK, 2018)
Objective: Procalcitonin (PCT), C-reactive protein (CRP), and leukocyte count are important host response biomarkers to determine the presence of infection. The aim of the present study was to evaluate the usefulness of PCT with other markers in lower respiratory tract infections. Methods: A total of 78 patients with community-acquired pneumonia (CAP), chronic obstructive pulmonary disease (COPD) exacerbations, and healthy controls were evaluated. Baseline serum levels of PCT and CRP and leukocyte counts were assessed and repeated on day 7 of antibiotic treatment. Results: Procalcitonin levels and absolute neutrophil counts (ANCs) were higher in the CAP and COPD groups than in the control group. In the CAP and COPD exacerbation groups, the leukocyte count, ANC, and CRP and PCT levels decreased on day 7 of the treatment (p<0.001). In the CAP group, the baseline PCT levels were correlated with leukocyte counts (r=0.495, p<0.005), ANCs (r=0.426, p<0.019), and CRP levels (r=0.515, p<0.004). In receiver operating characteristic curve analysis, PCT threshold >0.12 ng/mL had a sensitivity of 70.4% and specificity of 68.7%, and CRP threshold >22.9 mg/L had a sensitivity of 85.2% and specificity of 75.0%. Conclusion: Procalcitonin is a useful marker to determine the initiation of antibiotic therapy and can also be used to cease the treatment.
Keywords: Procalcitonin; C-reactive protein; lower respiratory tract infection; COMMUNITY-ACQUIRED PNEUMONIA; C-REACTIVE PROTEIN; SEVERE SEPSIS; SEVERITY; ADULTS; MANAGEMENT; GUIDELINES; MARKERS; DISEASE